2012
DOI: 10.1371/journal.pcbi.1002548
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Starvation in Yeast: Mechanisms of Homeostasis Revealed by Mathematical Modeling

Abstract: The intrinsic ability of cells to adapt to a wide range of environmental conditions is a fundamental process required for survival. Potassium is the most abundant cation in living cells and is required for essential cellular processes, including the regulation of cell volume, pH and protein synthesis. Yeast cells can grow from low micromolar to molar potassium concentrations and utilize sophisticated control mechanisms to keep the internal potassium concentration in a viable range. We developed a mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
1
44
0
3
Order By: Relevance
“…An important implication of this finding is that potassium's primary effect in metabolic regulation, at least in the presence of abundant ammonium ions, should be on signaling rather than upon simple enhancement of cytoplasmic enzyme activities. The same conclusion has also been reached via theoretical analysis of K ϩ transport in Saccharomyces (77,78). That seems like a sensible arrangement; given that K ϩ is a bulk constituent of cytoplasm (also partially sequestered in vacuoles), its actual concentration should respond only slowly to threats.…”
Section: Discussionsupporting
confidence: 52%
“…An important implication of this finding is that potassium's primary effect in metabolic regulation, at least in the presence of abundant ammonium ions, should be on signaling rather than upon simple enhancement of cytoplasmic enzyme activities. The same conclusion has also been reached via theoretical analysis of K ϩ transport in Saccharomyces (77,78). That seems like a sensible arrangement; given that K ϩ is a bulk constituent of cytoplasm (also partially sequestered in vacuoles), its actual concentration should respond only slowly to threats.…”
Section: Discussionsupporting
confidence: 52%
“…Protons are pumped out of the cell by Pma1; however, HCO 3 2 accumulates inside the cell and becomes a negative-charge sink that increases K + retention inside the cell. Experimental studies confirm that NCE103 expression increases under conditions of K + starvation (Kahm et al 2012) and also show that while cells maintain a minimal intracellular K + concentration, the amount of K + in a yeast cell varies as a function of extracellular K + concentration and is an example of nonperfect adaptation (Kahm et al 2012).…”
Section: Maintenance Of Intracellular K + Levelsmentioning
confidence: 93%
“…K + is continually taken up and extruded by cells, and both processes are important; membrane potential increases when potassium influx is crippled and decreases in cells defective for K + efflux (Madrid et al 1998;Kinclova-Zimmermannova et al 2006); furthermore, K + efflux systems are regulated in response to changes in the membrane potential . K + transport is also closely coordinated with H + -ATPase activity, and Pma1 is activated when K + uptake increases and also under K + starvation conditions (Seto- Young and Perlin 1991;Kahm et al 2012).…”
Section: The Alkali Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of systems biology, mathematical modelling predicting the complexity of ion regulation allowed the proposal of mechanisms of cation homeostasis (Kahm et al, 2012;Ke et al, 2013). Detailed comparisons between wild-type and trk1,2 double mutant strains showed that, in addition to the lack of high affinity K + -transport: (i) the mutants grown under non-limiting potassium were hyperpolarized and had a lower intracellular pH than the wildtype (Navarrete et al, 2010); (ii) regulation of the Trk1,2 system is important but not sufficient to achieve homeostasis, and adaptation to low potassium requires modulation of proton fluxes, production of bicarbonate and activation of the H + -ATPase (Kahm et al, 2012); and (iii) Trk1 is not essential for adaptation to external potassium changes since trk1,2 mutants are still able to adjust intracellular cation content in response to rapid changes in external potassium, although the dynamics of potassium exchange in the mutant are very different from the wild-type (Herrera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%